Study on the demand for family Takaful product in Senawang, Negeri Sembilan / Abdul Hadi Mohd Ghazali and Siti Nasuha Roslan - Mohd Ghazali, Abdul Hadi; Roslan, Siti Nasuha (Faculty of Business Management, 2016)
It was reported that Malaysia has experienced a low penetration rate for the Family Takaful business despite the many forms of incentives provided by the Government. The available literature that focuses on life assurance and related research on Family Takaful is rather scarce. In view of this, it must be mentioned that, this particular study is significant because it provides a critical insight and better understanding of the critical factors that actually determine the Family Takaful demand in Senawang, Negeri Sembilan. Thus, the main objective of this study is to determine the critical factors for Family Takaful demand in Senawang, Negeri Sembilan. The study involves a survey using structured questionnaires to solicit responses from people who have joined Family Takaful plans in selected leading Takaful companies. Data analysis involves the use of regression analysis. From a set of factors that contributed to the Family Takaful demand in this study, the result of regression analysis showed that product and services have significant relationship with family takaful demand.